Terpenoids, DEET and short chain fatty acids as toxicants and repellents for Rhyzopertha dominica (coleoptera: Bostrichidae) and Lasioderma serricorne (Coleoptera: Ptinidae). (May 2020) - Ramadan, Gomaa R.M.; Abdelgaleil, Samir A.M.; Shawir, Mohamed S.; El-bakary, Ahmed S.; Zhu, Kun Yan; Phillips, Thomas W.
Abstract: Plant-based products and common repellents have been suggested as promising alternatives for management of stored product insects. In this study, contact toxicity and repellent activity of the safe natural products carvacrol, citronella oil, geraniol, nootkatone, ocimene and R -(+)-pulegone, and the synthetic commercial repellents, N, N -Diethyl-3-methylbenzamide (DEET), and the fatty acid mixture of octanoic, nonanoic, and decanoic acids (C8910) were evaluated against the lesser grain borer, Rhyzopertha dominica and the cigarette beetle, Lasioderma serricorne under laboratory conditions. In contact toxicity assays the compounds were tested at concentrations ranging between 0.008 and 0.4 mg/cm 2 . Carvacrol and R -(+)-pulegone exhibited the highest contact toxicity with LC50 values of 0.019 and 0.023 mg/cm 2 against L. serricorne and LC50 values of 0.012 and 0.019 mg/cm 2 against R. dominica, respectively. Similarly, C8910, geraniol and citronella oil showed toxic effect against both insects. The repellent activity of compounds was tested using the preference method assay at concentrations ranging between 3.125 and 50.0 μg/cm 2 . The highest repellency percentage (RP) was achieved by C8910 against L. serr i corne with a RP value of 76.0% at the lowest concentration (6.25 μg/cm 2 ), while carvacrol showed the highest repellent activity against R. dominica with RP value of 88.0% at 3.125 μg/cm 2 within 3 h of insect exposure. The tested compounds caused higher repellent activity to R. dominica than L. serricorne . In vitro inhibition studies of acetylcholinesterase (AChE) in adults of both species showed that R-(+) pulegone strongly inhibited AChE activity of R. dominica and L. serricorne with 69.0% and 88.0% inhibition at 40 mM, respectively. Carvacrol caused 41.8% inhibition in AChE activity of R. dominica compared to 66.7% of L. serricorne at 40 mM. The results indicated that the tested natural compounds may be useful alternatives for controlling R. dominica and L. serricorne . Highlights: Carvacrol and R -(+)-pulegone were toxic against R. dominica and L. serricorne. C8910, a safe fatty acid mixture, was repellent against these two beetle species. R -(+)-pulegone strongly inhibited acetylcholinesterase in both species. Tested compounds are all regarded as safe for people and food. Some of these compounds could have stored product pest management applications.